The Influence of Knowledge on The Lifestyle of Diabetes Mellitus Patients at The Workplace of The Bengkuring Community Health Center, Samarinda - Syahrun, Syahrun; Metungku, Fanny; Solichin, Solichin; Arrizqi, Nur Aini Zulaikhah (Jurnal Kesehatan Pasak Bumi Kalimantan, 2024)
Background: Diabetes mellitus is a chronic condition because the pancreas is unable to produce insulin effectively.  The increase in DM cases can be caused by  lifestyle, lack of knowledge and inability to detect early, lack of physical activity and inappropriate regulation of food composition.  Purpose: to determine the influence  of the level of knowledge with lifestyle in DM sufferers. Method: using  quantitative methods with analytical descriptive design. The total population of 260 people, based on purposive sampling techniques according to  the inclusion criteria of DM type I and II without comorbidities, 100 samples were obtained. Iinstrument DKQ-24  for knowledge level and HPLP-II for lifestyle variables.  Data analysis using contingency coefficient with chi square test. Results: The majority suffered from DM for 6 – 10 years, had  a family history of DM, and had received previous education. The majority of  knowledge about DM is sufficient but those who have less knowledge are also quite a lot (43%) whose dominant lifestyle is categorized as quite healthy . Crosstab result the majority of the patient's knowledge level is at a sufficient  level who  have a fairly healthy lifestyle, tend to  have a less knowledge level but have a fairly healthy lifestyle (43%).  Analyze the value of r = 0.641 with p value < α. Conclusion: the level of knowledge affects lifestyle even though the patient has poor knowledge about DM